(untitled) (Balkan Journal of Applied Mathematics and Informatics, 2024)
This paper presents a comparative analysis of prominent BPMN (Business Process Model and Notation) tools, including Camunda, Bizagi Modeler, bpmn.io, ProcessMaker, and Lucidchart. We evaluate these tools based on key criteria such as features, functionality, usability, integration capabilities and cost. By examining their strengths and limitations, we aim to provide a comprehensive overview that assists organizations in selecting the most suitable tool for their business process modelling needs. The analysis includes practical insights into each tool’s effectiveness in facilitating process design, simulation and execution, offering valuable guidance for practitioners and decision-makers.